1988
DOI: 10.1159/000234660
|View full text |Cite
|
Sign up to set email alerts
|

Increased Superoxide Anion Production and Glutathione Peroxidase Activity in Peritoneal Macrophages from Autoimmune-Prone MRL/Mp-lpr/lpr Mice

Abstract: We studied the release of superoxide anion (O2––) in peritoneal macrophages from autoimmune-prone MRL/Mp-lpr/lpr (MRL/l) mice. Compared to resident peritoneal macrophages from control MRL/ Mp- +/+ (MRL/n) mice, macrophages from MRL/l mice exhibited an age-related increase of spontaneous and PMA-induced O2–– secretion in association with the development of the autoimmune process. Analysis of the kinetic parameters of NADPH oxidase in macrophages revealed that MRL/l ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Rokutan et al [42] showed increased oxygen intermediates in the organs from MRL/lpr mice, whereas reduced serum levels of antioxidants and radical scavengers have been reported in human SLE [43]. Treatment with antioxidants, such as vitamin E, suppressed circulating anti-dsDNA antibody levels and the development of renal disease [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rokutan et al [42] showed increased oxygen intermediates in the organs from MRL/lpr mice, whereas reduced serum levels of antioxidants and radical scavengers have been reported in human SLE [43]. Treatment with antioxidants, such as vitamin E, suppressed circulating anti-dsDNA antibody levels and the development of renal disease [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Possible implications of superoxides in SLE have been demonstrated [42][43][44]. Rokutan et al [42] showed increased oxygen intermediates in the organs from MRL/lpr mice, whereas reduced serum levels of antioxidants and radical scavengers have been reported in human SLE [43].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of oxidative stress have previously been associated with various pathological conditions (8--10), but the role of an impaired or defective antioxidant defense system in autoimmune diseases has been explored only to a limited extent (11)(12)(13). Our recent study on MRL/lpr mice indicated that along with other immunological abnormalities, these mice clearly showed a defective antioxidant defense system as the expression of hepatic antioxidant enzymes was significantly lower when compared to that of an MRL/+ strain (14).…”
Section: Lipids 29 561-568 (1994)mentioning
confidence: 99%
“…Other work has suggested a role for cells not of bone marrow origin in the development of 1pr lymphadenopathy (36)(37)(38) ensues, leading to lymphoid depletion and early mortality (39,40) . If, however, an lpr lymph node is also transplanted, these mice will develop adenopathy in that transplanted node (38), suggesting that nonhemopoietic cells may be necessary for full expression of the T cell defect .…”
Section: Serum Autoantibody Levelsmentioning
confidence: 99%